The Correlation Between Students' Self-Confidence and Speaking Ability at SMA Negeri 1 Peling Tengah - Nurhaida Lakuana; ST. Marhana Rullu (BABASAL English Education Journal, 2022)
The purpose of this research was to determine the correlation between students’ self-confidence and speaking ability at SMA Negeri 1 Peling Tengah. The design of this research was quantitative research with the name correlational design. The population of this research were students of class XI SMA Negeri 1 Peling Tengah and the sample was class XI science students, totaling 25 students. In collecting data, the researcher used a questionnaire and speaking scores from the English teacher. The researcher used SPSS 23 for the correlation between students’ self-confidence and speaking ability. After analyzing the questionnaire data, the result or rxy of 0.87 were obtained, the results of a signifinance level of 5% from rtable were 0.413. Therefore the rxy value was higher than the rtable value; 0.87>0.413. It is assumed that there is a correlation between students’ self-confidence and speaking ability at SMA Negeri 1 Peling Tengah in the academic year of 2021. The level of correlation coefficient between variable X and variable Y is 87%, which is a very high correlation or has a correlation.